Sociology Approach in Food Souvenir Innovation: The Customer-Producers Relation on Online Marketing Communication - Purnomo, Agustina Multi; Musyafi, Reza Ahmad (Universitas Djuanda, 2022)
Limited customer and producer relations research develops various food souvenir products through online marketing communication. This research focused on the actions of food providers in developing food souvenir innovation as a result of interaction with customers through the online marketing communication medium. This research differs from previous research on media interaction and focuses on consumer response as the driving force for the innovation process on food. This study used qualitative research that analyzed one online souvenir food shop as the study case. The interviews and observations data are grouped based on a theory with a narrow interpretation or deductive approach. The data is presented in the form of interview quotes, sample images of data sources, and limited understanding according to the appearance of the data. The study found that customer and producer relations in online marketing communication did not encourage innovation for food souvenirs. The interaction between food providers and Instagram followers was more accurately described as an interaction in the form of product purchases. The actions of food providers in developing new products result from relations between actors and other selling actors in the form of reactions to similar food development trends. Creating fresh foods as the result of innovative action follows the trend of similar products in the development of Bogor's online food souvenir market